Effects of gun ban policy implementation to gun-related electoral violence during 2010 presidential election a comparative case study of the Municipality of Pulupandan and Escalante City. - Palencia, Maycee d.R
This research study is a comparative qualitative study that looked into the effects of gun ban policy implementation to gun-related electoral violence in the Municipality of Pulupandan and Escalante City during 2010 Presidential Election. Crime control model is used in determining and analyzing the relationship of the variables, gun ban policy implementation (independent variable) and gun-related electoral violence (dependent variable). The researchers conducted in-depth interviews with 19 respondents and did an archival research of the available documents relevant to the study in the implementing agencies. though there is no record incidence of gun-related and other forms of electoral violence in the two locales during the period of gun ban policy implementation, the study cannot directly establish that the non-occurrence of gun-related and other forms of electoral violence is primarily due to the implemented gun ban policy. Deterrence of the probable perpetrators and difficulties encountered by the implementing agencies could have been the other factors which led to the non-occurence of electoral violence in the two locales during 2010 Presidential election.